The Influence of Time Management and Learning Media on Academic Achievement of Office Administration Education Study Program Students - Ellys Siregar (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
This study aims to determine whether there is an effect of time management and learning media on academic achievement of academic colleges 2018 State University of Medan. The research is an ex-post facto. The population in this study were all students of the 2018 Administration Education Study Program At The University Of Medan with a total 59 students. The sampling technique in this study used a total sampling technique with a sampleof 59 respondents. The data analysis technique used was normality, linearity test, multicolinearity test, multiple regression analysis, coefficient of determination, and to test hypothesis used the T test, this test was carried out to measure the effect partially,whle to measure the effect simultaneously the F test was used. There is a positive and significant influence between time management on academic achievement of students of the 2018 Economic Administration Education Study Program At A State University.